Penerapan Mikrokontroler Arduino Uno pada Desain Perancangan Sistem Ayunan Bayi Otomatis - Agung Pratama; Poningsih; Sundari Retno Andani; Solikhun; Anjar Wanto (Journal of Informatics Management and Information Technology, 2021)
A baby swing is one of the objects commonly used by mothers to help put their babies to sleep. Starting from mothers who live in big cities to remote villages, they are familiar with baby swings. Usually, babies fall asleep quickly when sleeping in a swing. Another reason is that the baby can sleep longer, so the mother can do other unfinished activities. This research aims to design the design of an automatic baby swing system using the Arduino Uno R3 microcontroller Atmega 328. The assembly process of this tool uses a combination of the Arduino Uno R3 microcontroller with sound sensors, servo motors, led lights, and several supporting components such as jumper cables, boards, and others. Based on the experimental results, this tool can be used as a control system for the baby's swing, so that the swing will automatically move on its own when the baby cries, so that the baby can fall back asleep. So it can be concluded that with this automatic baby swing, it will help ease the work of a mother who wants to do other work.